Rancang Bangun Sistem Informasi E-Commerce Berbasis Web Studi Kasus PT. Delambrands Kharisma Busana - Priambodo, Priambodo; Sharyanto, Sharyanto; Sudarsono, Bernadus Gunawan (Journal of Engineering, Technology and Computing (JETCom), 2024)
PT. Delamibrands Kharisma Busana is a retail company specializing in the sale of fashion products, such as clothing and accessories. The company emphasizes the importance of customer trust and satisfaction to meet their needs and enhance the company's economic performance. Currently, PT. Delamibrands Kharisma Busana employs traditional sales methods, requiring customers to visit physical stores in malls to shop. This can lead to uncertainty regarding product availability, potentially diminishing customer loyalty. Additionally, the company faces challenges in expanding its product marketing reach to various regions, both within and outside the city. Therefore, an e-commerce information system has been developed to address these issues. This information system uses the PHP programming language, MySQL database, UML modeling, and the Waterfall method as the SDLC methodology.